2000
DOI: 10.1002/(sici)1097-4628(20000321)75:12<1480::aid-app6>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity and magnetoresistivity of protonic acid (h2SO4 and HCl)-doped polyaniline at low temperature

Abstract: Electrical-transport properties of protonic acid (H 2 SO 4 and HCl)-doped polyaniline (PANI) in an aqueous ethanol medium were investigated in the temperature range 1.8 K Յ T Յ 300 K and in a magnetic field up to 8 T. The room-temperature resistivity of HCl-doped PANI is larger than that of H 2 SO 4 -doped PANI. The resistivity ratios r ϭ (1.8 K)/(300 K) of the samples are high. The samples in the insulating region show a crossover from a Mott to an Efros-Shklovskii variable range hopping conduction at T ϭ 9.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The dc resistivity of different PANI-Co samples has been measured in the temperature range of 77 T 300 K. The room temperature resistivity ρ(300 K) of the investigated PANI-Co samples varies between 0.013 and 0.061 cm and is listed in table 1. In our previous study [32], it was observed that room temperature resistivity of PANI-HCl is 0.080 cm and that of PANI-H 2 SO 4 is 0.105 cm. So the introduction of Co atoms within PANI only slightly reduces its resistivity.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The dc resistivity of different PANI-Co samples has been measured in the temperature range of 77 T 300 K. The room temperature resistivity ρ(300 K) of the investigated PANI-Co samples varies between 0.013 and 0.061 cm and is listed in table 1. In our previous study [32], it was observed that room temperature resistivity of PANI-HCl is 0.080 cm and that of PANI-H 2 SO 4 is 0.105 cm. So the introduction of Co atoms within PANI only slightly reduces its resistivity.…”
Section: Resultsmentioning
confidence: 87%
“…They have studied the effect of ZnCl 2 on the transport properties of PANI-HCl. Ghosh et al [32] have studied the electron transport properties of HCl doped PANI. They observed a transition from 3D Mott (T 1/4 ) to Efros-Shoklovskii (T 1/2 ) in the temperature dependent conductivity at 10 K. Lu et al [33] have studied the hysteresis loop at room temperature of PANI-Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the variation of magnetoconductivity with magnetic field of different samples at 200 K. All of the samples showed positive magnetoconductivity, whereas the HCl‐ and H 2 SO 4 ‐doped PANI showed negative magnetoconductivity 23. According to VRH theory, conductivity in the presence of a magnetic field can be explained by two mechanisms, such as the wave function shrinkage model51–55 and orbital magnetoconductivity theory 56–58.…”
Section: Resultsmentioning
confidence: 99%
“…Pure polymers can be classified as insulating or noncrystalline semiconducting materials with very low charge carrier mobilities. Doping renders it a good conductor due to the delocalization of charge and spin along the backbone of the polymer 15–25. The electrical conductivity of PANI is affected most by doping and medium, and many investigations have been carried out on doped PANI during the last few decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation